2013
DOI: 10.1007/s11060-013-1207-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CD147 in patients with glioblastoma

Abstract: CD147, also known as extracellular matrix metalloproteinase inducer, is a widely distributed cell surface glycoprotein that belongs to the immunoglobulin superfamily. CD147 has been proved to be enriched on the surface of many tumor cells, promoting tumor growth, invasion and metastasis by its stimulation effect on adjacent fibroblasts to produce matrix metalloproteinases. In this study, we aimed to explore the expression pattern of CD147 in glioblastoma (GBM) and investigate whether it could be used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
0
30
0
3
Order By: Relevance
“…CD147 is central in the promotion of tumor invasion, growth/progression and metastasis because it up-regulates MMPs secreted from adjacent fibroblasts [98] through mostly unknown mechanisms. MMPs stimulated by CD147 degrade the extracellular matrix [99] and underlie tumorigenesis, while many of the proinflammatory cytokines and other mediators production stimulated by CD147 have also been directly linked to cancer [52,76].…”
Section: The Expression and Role Of Cd147 In Tumor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD147 is central in the promotion of tumor invasion, growth/progression and metastasis because it up-regulates MMPs secreted from adjacent fibroblasts [98] through mostly unknown mechanisms. MMPs stimulated by CD147 degrade the extracellular matrix [99] and underlie tumorigenesis, while many of the proinflammatory cytokines and other mediators production stimulated by CD147 have also been directly linked to cancer [52,76].…”
Section: The Expression and Role Of Cd147 In Tumor Cellsmentioning
confidence: 99%
“…Indeed, CD147 has been suggested as a prognostic marker in endometrial cancer [65], gastric cancer [96], glioblastoma [98], HCC [78], lupus nephritis [130], UCB [94] and other diseases. Patients with high CD147 expression have a poor prognosis [104], while multivariate analysis revealed that the expression of CD147 is an independent prognostic factor for patients with NSCLC [81,176].…”
Section: Clinical Applications Of Cd147mentioning
confidence: 99%
See 1 more Smart Citation
“…CD147 can also degrade the basement membrane and consequently promote tumor invasion. It is reported that CD147 is highly expressed in various malignant tumors and is associated with survival outcomes [1016]. Previous studies also investigated the relationship between CD147 and NSCLC prognosis, however, those results were controversial [17–26].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies demonstrated that the CD147 molecule was highly expressed on the surface of various cancer cells, including cancers of the liver, lung, breast, kidney, colon, prostate, and esophagus [12]. There is emerging evidence indicating that CD147 plays a central role in the progression of many cancers due to increased adhesion, migration, invasion, and matrix metalloproteinases [13–16]. Importantly, increased expression of cancer-associated CD147 predicts aggressive behavior and poor prognosis [12, 1720].…”
Section: Introductionmentioning
confidence: 99%